IMPROVEMENT OF DESCRIPTION WRITING SKILLS THE TENTH GRADER STUDENTS OF SENIOR HIGH SCHOOL 1 MARON OF PROBOLINGGO THROUGH THE INQUIRY STRATEGY - Nanik Andayani (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2021)
This research is a qualitative research that designed to uses the class action research (CAR). This research was conducted in the ten grader the students of Senior High School I Maron Probolinggo unnecessary to make the teaching and learning programs that have been designed. The researcher is the teacher of the ten grader the students of Senior High School I Maron Probolinggo. Therefore, besides the teacher as researcher, the teacher also as observer. However, to overcome the limitations of the teacher they do observation, they asked their friends and colleagues to become an observer also serves as a collaborator.The main problem of this research is the “How to improve the writing description skills of ten grader the students Senior High School I Maron through inquiry strategy ?” the problem break down into three things, (1) how did the improvement process of learning to write the description of the ten grader the students of Senior High School I Maron Probolinggo through inquiry strategy? (2) how do you learn to write the description of the results that is increase in the ten grader the students of Senior High School I Maron Probolinggo through inquiry strategy?                     The results showed as follows. (1) there has been an increase in the process of learning to write description through inquiry strategy. The activities that may include the pre-write stage, To develop the outline of, revision, and editing. The implementation of this class action is recorded and observed by the researchers but before the execution of the cycle I course of research had not reached yet the desired goal because the achieved results is not perfection yet. In the Cycle I, the process of learning to description writing through the inquiry strategy has been good and interesting but still found that need to get attention with regards to the class action research. While the processing of learning to description writing cycle II through inquiry strategy has been very good, (2)    The improvement in the achievement of learning to write the description appears that if before the application of cycle I the students who have not achieved completion or who obtained a score below 70 as many as 21 children or 61.8%, in cycle I that decreased to 8 or 23.5% , and in cycle II the student's score was above 70. The completion increased from 13 children or 38.2% at the first reflection to 26 children or 76.5% in cycle I, and it is increased to 34 children or 100% in cycle II. The lowest value at the first reflection and cycle I is the same as 60 and in cycle II it is increases to 70. The highest score is increased from 75 at the first reflection to 85 in cycle I and it is increased to 90 in cycle II. The classical average is increased from 66.6 to 71.5 and it is also increased to 76.2 in cycle II.